Strategi Dakwah Kiai Akhid Ismani Dalam Meningkatkan Religiusitas Masyarakat Tlogoharum Pati - Uswatus Niswah; Nurbini; Ahmad Zainuri (Journal of Islamic Management, 2023)
The strategy of Da'wah Kiai Akhid Ismani in an effort to increase the religiosity of the Tlogoharum Pati community is carried out by fostering a person's sense of religion so that they can carry out their social role with commendable morals, distinguish between good and bad, and make it a source of guidance in living. The results showed that the proselytizing strategy used by Kiai Akhid Ismani in an effort to increase community religiosity was carried out through the field of communication which was applied in routine recitation activities once a week and also through the field of art in the form of tambourine. The data mining technique is carried out by means of observation, interviews, and documentation. Meanwhile, data analysis techniques with the Miles and Huberman model, namely through the stages of data reduction, data exposure or display, data verification and drawing conclusions.